2017
DOI: 10.1186/s12915-017-0347-9
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-like aggregation of provasopressin in diabetes insipidus and secretory granule sorting

Abstract: BackgroundAggregation of peptide hormone precursors in the trans-Golgi network is an essential process in the biogenesis of secretory granules in endocrine cells. It has recently been proposed that this aggregation corresponds to the formation of functional amyloids. Our previous finding that dominant mutations in provasopressin, which cause cell degeneration and diabetes insipidus, prevent native folding and produce fibrillar aggregates in the endoplasmic reticulum (ER) might thus reflect mislocalized amyloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…Both WT and some human proAVP mutants were shown to be substrates of Sel1L-Hrd1 ERAD. In Sel1L-null N2a cells, both WT and mutant proAVP appeared to accumulate in amyloid-like fibrillar structures, similar to what has been previously observed for human AVP mutants (10).…”
Section: Avp Erad and Autosomal Dominant Central Diabetes Insipidussupporting
confidence: 57%
See 1 more Smart Citation
“…Both WT and some human proAVP mutants were shown to be substrates of Sel1L-Hrd1 ERAD. In Sel1L-null N2a cells, both WT and mutant proAVP appeared to accumulate in amyloid-like fibrillar structures, similar to what has been previously observed for human AVP mutants (10).…”
Section: Avp Erad and Autosomal Dominant Central Diabetes Insipidussupporting
confidence: 57%
“…In mammals, the most well-characterized ERAD machinery is the highly conserved complex of suppressor-enhancer of lin-12-like and hydroxymethylglutaryl-CoA reductase degradation protein 1 (SEL1L-HRD1), which consists of the E3 ubiquitin ligase HRD1 and its adaptor protein SEL1Lc ( Figure 1B). In this issue Shi et al (10). Both WT and some human proAVP mutants were shown to be substrates of Sel1L-Hrd1 ERAD.…”
Section: Avp Erad and Autosomal Dominant Central Diabetes Insipidusmentioning
confidence: 99%
“…While the detailed mechanism of proprotein sorting into SGs is not well established, it is clear that signal-mediated sorting and congregation-aggregation of regulated cargoes contribute to the biogenesis of SGs (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 On the other hand, it has been found that a variety of nonpathogenic proteins could also form amyloid fibrils with normal biological functions, indicating that formation of amyloid fibrils is a prevailing phenomenon in nature. [4][5][6] Amyloidogenic proteins or polypeptides usually came from different tissues and showed very little similarity considering their full amino acid sequences, but the amyloid fibrils they formed shared several characteristic features such as similar morphology, apple-green birefringence after Congo red (CR) staining, and specific fluorescence when binding with thioflavin-T (ThT), suggesting that there might be a common mechanism for the formation of amyloid fibrils by these different proteins or polypeptides.…”
Section: Introductionmentioning
confidence: 99%